2010
DOI: 10.1021/la100049s
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Molecular Mechanisms of Quartz-Binding Peptides

Abstract: Understanding the mechanisms of biomineralization and the realization of biology-inspired inorganic materials formation largely depends on our ability to manipulate peptide/solid interfacial interactions. Material interfaces and biointerfaces are critical sites for bioinorganic synthesis, surface diffusion, and molecular recognition. Recently adapted biocombinatorial techniques permit the isolation of peptides recognizing inorganic solids that are used as molecular building blocks, for example, as synthesizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 44 publications
13
95
1
Order By: Relevance
“…Biocombinatorial techniques that were developped to select the «best» peptide sequences binding to a particular biochemical target have been applied to choose the best sequences for adsorption on inorganic surfaces. 271 In this way, quartz-binding peptides have been engineered 272 and sequences specific for amorphous silica have also been produced. 273 These studies are quickly generating a database of specific peptide sequences having more or less strong affinity with silica surfaces.…”
Section: From Oligopeptides To Proteins: Adsorption Secondary Structmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocombinatorial techniques that were developped to select the «best» peptide sequences binding to a particular biochemical target have been applied to choose the best sequences for adsorption on inorganic surfaces. 271 In this way, quartz-binding peptides have been engineered 272 and sequences specific for amorphous silica have also been produced. 273 These studies are quickly generating a database of specific peptide sequences having more or less strong affinity with silica surfaces.…”
Section: From Oligopeptides To Proteins: Adsorption Secondary Structmentioning
confidence: 99%
“…In order to evaluate the role of these residues in the interaction, classical MD simulations (CHARMM force field) of three peptides (two strong-binders and one weak-binder) in interaction with quartz (100) surface were carried out. 272,676 It was found that the strong-binding peptides exhibited the Pro-rich regions in close proximity to silica surface, and visual inspection revealed that these residues were buried at interstitial sites of quartz, whereas polar groups (Ser, His and C-terminus carboxylate)…”
Section: Interaction With Peptidesmentioning
confidence: 99%
“…19,[73][74][75][76] Sequence similarity is entirely random (5%) when the pH value varies in addition. Specific models for a given type of silica and conditions in solution are thus essential 19 and proposed here to cover the range of possible surface chemistry and ionization (Table 2).…”
Section: A Silica Surface Model Databasementioning
confidence: 99%
“…A FF based on the CHARMM FF was parameterized by Lopes et al (2006) to obtain a structural and dynamic representation of water in the vicinity of neutral quartz crystalline surfaces using MD simulations. This FF was used for a set of peptides known to be strong and weak binders to the quartz (100) surface and showed that Pro, Trp and Leu were the main residues forming close contacts with the surface (Oren et al 2010).…”
Section: (2012)mentioning
confidence: 99%
“…REMD methods are useful to sample a large set of configurations in different potential wells separated by high energy barriers, which otherwise is not possible in a classical MD simulation. Indeed, temperature-based REMD (T-REMD) simulations were used in several studies to accelerate the sampling of peptide-surface interactions Li et al 2011;Oren et al 2010) and of interactions of basic fibroblast growth factor (bFGF), a small protein, with a hydroxyapatite (001) surface (Liao & Zhou, 2014). Liao and Zhou observed that while the protein displaces the surface hydration shell and binds tightly to the surface in the T-REMD simulations (five replicas in the range from 310 K to 2500 K), bFGF did not contact the surface directly in classical MD simulations at 310 K (Liao & Zhou, 2014).…”
Section: Molecular Dynamicsmentioning
confidence: 99%